2019
DOI: 10.1021/acs.jafc.8b05032
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Efficiency of Green Tea and Its Components on Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a typical chronic liver disease highly correlated with metabolic syndrome. Growing prevalence of NAFLD is supposed to be linked with the unhealthy lifestyle, especially high-calorie diet and lacking enough exercise. Currently, there is no validated pharmacological therapy for NAFLD except for weight reduction. However, many dietary strategies had preventive effects on the development of liver steatosis or its progression. As one of the most common beverages, green te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 110 publications
4
40
0
Order By: Relevance
“…It is because tea contains plenty of pharmacologically active molecules that is why it has been used for various health benefits. For instance, these bioactive constituents in green tea were proved to alleviate the risk of nonalcoholic fatty liver disease (Zhou et al, 2019). Tea catechins pose beneficial effects in the prevention of carcinogenesis and cardiometabolic diseases, have been well documented (Yang & Zhang, 2019).…”
mentioning
confidence: 99%
“…It is because tea contains plenty of pharmacologically active molecules that is why it has been used for various health benefits. For instance, these bioactive constituents in green tea were proved to alleviate the risk of nonalcoholic fatty liver disease (Zhou et al, 2019). Tea catechins pose beneficial effects in the prevention of carcinogenesis and cardiometabolic diseases, have been well documented (Yang & Zhang, 2019).…”
mentioning
confidence: 99%
“…In addition, we found a significant inverse association between total polyphenol intake and mortality from digestive disease. It was reported that coffee and green tea could exert such beneficial effects on liver and bowel diseases [39][40][41][42][43]. Further studies evaluating associations between polyphenol intake and digestive disease are awaited.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the antioxidant capacity of EF-D seems to have an important connection with treating NAFLD. It has been reported that polyphenols through activation of Nrf2-ARE signal pathways respond to oxidative stress for inhibiting lipid accumulation [ 40 ]. Furthermore, Nrf2 promotes the activation of downstream relative target genes, such as HO-1, NQO1, CAT, and GSTA2, leading to improved oxidative stress resistance [ 41 ].…”
Section: Discussionmentioning
confidence: 99%